Problems with the Classification and Recognition of Intangible Assets - Gaižauskas, Lionius; Budrionytė, Ramunė (Ekonomika, 2003)
This article analyses the problems with the classification of intangibles and their recognition in the accounting statements. Intangibles are one of the most complex issues in accounting due to the difficulties in identifying them, estimating their value and determining their economic life.The importance of intangibles increased significantly over the past 15-20 years. The growth of high-technology companies exposed the increasing difference between market capitalisation and book value of the company. At the same time traditional accounting did not reveal those differences in the accounting statements. The increase in the market capitalisation was attributed to the intangible assets, most of which are not accounted in traditional accounting system. However, this situation dissatisfies both accounting information users and companies’ management Therefore new methods to incorporate intangibles into the accounting statements and management reports should be found.The article presents the traditional classification of intangibles and their recognition criteria in the modem accounting system. The concept of “intellectual capital” and its elements arc presented. Main types of intellectual capital are introduced: human capital, organisational capital, client capital and intellectual property. Only intellectual property is recognised as an asset and presented in accounting statements.Since it is very difficult to evaluate intellectual capital, presenting intellectual capital in the accounting statements can result in misleading information. Therefore, authors suggest that for the external users the information about intangibles should be presented in the notes to the accounts. However, it is important to identify and classify the data about intangibles for the managerial purposes. This information should be used to achieve the operational and strategic objectives.